Necesidad de regular los contratos de ínfima cuantía realizados por Los Gobiernos Autónomos Descentralizados, a fin de implementar el informe precontractual de la Contraloría General del Estado - Elizalde Granda, Juan Bautista (2015)
This research is titled : " NEED REGULAR smallest amount CONTRACTS MADE BY GOVERNMENTS autonomous decentralized ORDER TO IMPLEMENT THE REPORT OF THE COMPTROLLER GENERAL PRECONTRACTUAL STATE " , the same that addresses the problems related to the violation of several constitutional and legal professionals in relation to public procurement contracts within the smallest amount by Autonomous Decentralized Governments rights , is also a pre report by Comptroller is not required, allowing corruption and addressing of these contracts are for groups or corrupt professional detriment of others. The hypothesis that I lead is you work research was as follows: The National Procurement System (INCOP) does not provide for pre - contractual report issued by the Comptroller General, in reference to contracts smallest amount made by the Regional Governments Decentralized, for the provision of public goods and services, limiting processes of transparency and social control. The processes used were hypothetical, inductive - deductive method, explanatory analytical, statistical, for the development of the descriptive analysis method was used. The techniques were applied was the survey of 30 legal professionals in private practice, through the instrument consisted of questions designed to obtain relevant information. Among the outstanding results we have through study and doctrinal and legal analysis of the issues raised , it is shown that there are flaws in the law, so it is necessary to modify or update the Act in respect of contracts smallest amount handling Autonomous Decentralized Governments , hurting many professionals compete and access such contracts